Vitamin D levels in children with celiac disease - T.V. Sorokman; N.O. Popelyuk; D.I. Koliesnik; І.S. Sokolnyk (Zaslavsky O.Yu., 2021)
Background. A significant increase in understanding of the role of vitamin D in the body, more effective detection of celiac disease, and the need to monitor the health of children against the background of long-term adherence to a gluten-free diet were prerequisites for our study. The study was aimed to analyze the level of vitamin D in children with celiac disease. Materials and methods. The results of the examination of 29 children aged from 6 months to 18 years with a verified diagnosis of celiac disease were analyzed. Serum vitamin D levels were measured by the electrochemiluminescent method (Roche Diagnostics GmBH, Mannheim, Germany). The results of vitamin D supplementation in patients with celiac disease were compared with the control group of 30 healthy children aged from 1 to 18. Mathematical processing of the material included a standard algorithm for statistical research using Microsoft Excel 2016, Attestat. Results. Among the patients included in the study, typical celiac disease was found in 24 (82.7 %) cases, which is 4.8 times more common than atypical - in 5 (17.4 %) children. The gastrointestinal symptoms dominated in a clinical picture. Manifestation of the disease in most patients was observed in the first year of life - in 17 (58.6 %) cases, in 7 (24.1 %) patients aged from 1 to 3 years, and only in 5 (17.4 %) children older than 3 years. The average rate of vitamin D in children with celiac disease was probably lower than in healthy children and accounted for 24.4 ± 1.2; 21.2 [16.45-35.21] ng/ml. The number of children with normal vitamin D content is the highest among young patients, while the frequency of vitamin D deficiency is the lowest. The median serum vitamin D in patients on a gluten-free diet was 1.4 times higher (p < 0.05) than in the acute period, but 1.3 times lower (p < 0.05) than in the control group. Adherence to a gluten-free diet leads to increased levels of vitamin D but does not allow reaching the level in healthy children. Conclusions. Vitamin D deficiency is registered in children with celiac disease. All patients with celiac disease, regardless of the stage of the disease and adherence to a gluten-free diet, need to be monitored for vitamin D levels.